Transcriptome‐based analyses of phosphite‐mediated suppression of rust pathogens Puccinia emaculata and Phakopsora pachyrhizi and functional characterization of selected fungal target genes. (6th February 2018) - Gill, Upinder S.; Sun, Liang; Rustgi, Sachin; Tang, Yuhong; von Wettstein, Diter; Mysore, Kirankumar S.
Summary: Phosphite (Phi) is used commercially to manage diseases mainly caused by oomycetes, primarily due to its low cost compared with other fungicides and its persistent control of oomycetous pathogens. We explored the use of Phi in controlling the fungal pathogens Puccinia emaculata and Phakopsora pachyrhizi, the causal agents of switchgrass rust and Asian soybean rust, respectively. Phi primes host defenses and efficiently inhibits the growth of P. emaculata, P. pachyrhizi and several other fungal pathogens tested. To understand these Phi‐mediated effects, a detailed molecular analysis was undertaken in both the host and the pathogen. Transcriptomic studies in switchgrass revealed that Phi activates plant defense signaling as early as 1 h after application by increasing the expression of several cytoplasmic and membrane receptor‐like kinases and defense‐related genes within 24 h of application. Unlike in oomycetes, RNA sequencing of P. emaculata and P. pachyrhizi did not exhibit Phi‐mediated retardation of cell wall biosynthesis. The genes with reduced expression in either or both rust fungi belonged to functional categories such as ribosomal protein, actin, RNA‐dependent RNA polymerase, and aldehyde dehydrogenase. A few P. emaculata genes that had reduced expression upon Phi treatment were further characterized. Application of double‐stranded RNAs specific to P. emaculata genes encoding glutamate N ‐acetyltransferase and cystathionine gamma‐synthase to switchgrass leaves resulted in reduced disease severity upon P. emaculata inoculation, suggesting their role in pathogen survival and/or pathogenesis. Significance Statement: Phosphite (Phi) is an important low‐input chemical used against oomycete pathogens, and understanding its mode of action against fungal pathogens will have great implications for the development of novel fungicides. To achieve this, first the role of Phi in controlling rust pathogens was studied, secondly Phi‐mediated transcriptional alterations taking place in both host and pathogen were monitored, and finally several Phi‐targeted rust genes were validated by spraying plants with corresponding double‐stranded RNAs.